Voltage stability analysis taking into account a shunt connected device based on power electronics (2011)
In this paper the power system voltage stability problem is analyzed with active power–voltage (PV) curves, as a voltage compensator is introduced. The PV curves’ shape has been a subject of great concern, especially when voltage compensators are incorporated. Nevertheless, when such devices are taken into account, ordinarily the power electronic devices’ commutation it is not considered in detail. This paper proposes a shunt connected voltage compensator model that gives careful consideration to commutation dynamics. Through load variations, simulations are carried out for building the PV curves. Additionally, the field over-current protection in generators is taken into account in order to evaluate its impact on the aforementioned curves. A single-phase equivalent shunt compensator, and the proposed model, is simulated in a small power system. Results are exhibited, which show particularities that arise due to the proposed model.